Type II band alignment in Ge1-x-ySixSny/Ge1-α-βSiαSnβ heterojunctions. (February 2018) - Dey, Swagata; Mukhopadhyay, Bratati; Sen, Gopa; Basu, P.K.
Abstract: We have examined type II band alignment in Ge1-x-y Six Sny /Ge1-α-β Siα Sβ heterojunctions grown on virtual substrates in Si platform. It is found that, for different values of x, y, α and β, direct band gap type II band line up can be achieved for both tensile and compressive strains. The calculated band gap energy corresponds to the mid infrared to far infrared regions in the electromagnetic spectrum. Highlights: Crossover from direct to indirect bandgap occurs in GeSn for more than 8% Sn. This nature can be achieved using strain also. Due to several advantages, it is necessary to investigate the formation of type II structures with group IV semiconductors. Here, we have shown that, type II direct band gap nature can be realized with strained GeSiSn layer with less than 25% Sn.